Technical Design of Danish Seine on North Java Waters - Suparman Sasmita; Sulaeman Martasuganda; Ari Purbayanto (JURNAL PERIKANAN DAN KELAUTAN, 2012)
Cantrang (danish seine) is the most fishing gear used by fisheries along the coast of north java waters. The Ministry of Marine and Fisheries Affair of fishing gears regulation number 02/MEN/2011, cantrang operation areas more than areas 2 or 3 miles. They are using various size and design construction in each location. This paper would be descripting the design and construction of cantrang and comparing with Indonesian Standard (SNI) 01-7236-2006. The comparative value of net wing from Tegal more long than total length of net, circumference of mouth net cantrang Rembang approximately 60,84 meters more large than total length. The panel of webbing cantrang from Tegal has appropriate standar. Fishing ground of cantrangs are spread in north java waters approximately 30 – 60 meters. The operation of cantrang is all of year every day, especially when the wind condition from the east to the west areas, and sometimes they are operation in coastal area. Considering of comparation data, design and construction of fishing gear as cantrang from Brondong and Rembang are not related with SNI 01-7236-2006.Keyword: cantrang, danish seine, design, construction, webbing